FACTORS AFFECTING INTEGRATION OF RESETTLED PERSONS: A CASE OF RONGAI LOCATION NAKURU COUNTY, KENYA - MUCHERU, ELIZABETH WACHU; MURENGA, HADIJA; Mwangi, Samson Wokabi (Advances in Social Sciences Research Journal, 2020)
This study sought to investigate factors that affected integration between resettled persons and the host community in Rongai Location, Nakuru County, Kenya. The study employed purposive and stratified random sampling in selecting the sample size of 196 respondents. The study was guided by the Acculturation model which explains the conditions that need to be embraced by the host and resettled persons for effective community integration and participation in socio-economic livelihoods. The study employed a Survey Design and data was collected through interview schedules. Data was analyzed using descriptive statistics. According to the study, resource sharing, community trust, utilization of collective action, and dispute resolution mechanisms were all cited as important factors that could affect integration between the Host and the Resettled Persons. The study found that minimal resource sharing, low community trust, low utilization of collective action and adoption of divisive dispute resolution mechanisms all pointed to low integration between Resettled Persons and Host community. The study recommends for involvement of the hosting communities in decision making concerning resettlement and resource allocation for Internally Displaced Persons (IDPs) in the resettlement process. The study also recommends the application of legal framework in resettlement and reintegration. This includes using the guidelines provided for in the Kenya’s National Policy on the Prevention of Internal Displacement, Protection and Assistance to Internally Displaced Persons of August 2011 and The UN Guiding Principles on Reintegration (UGPR).